Astragalin Alleviates Neuropathic Pain by Suppressing P2X4-Mediated Signaling in the Dorsal Root Ganglia of Rats - Wang, Mengke; Cai, Xia; Wang, Yueying; Li, Shizhen; Wang, Na; Sun, Rui; Xing, Jingming; Liang, Shangdong; Liu, Shuangmei (Frontiers in Neuroscience, 2021)
Neurologic damage often leads to neuropathic pain, for which there are no effective treatments owing to its complex pathogenesis. The purinergic receptor P2X4 is closely associated with neuropathic pain. Astragalin (AST), a compound that is used in traditional Chinese medicine, has protective effects against allergic dermatitis and neuronal injury but its mechanism of action is not well understood. The present study investigated whether AST can alleviate neuropathic pain in a rat model established by chronic constriction injury (CCI) to the sciatic nerve. The model rats exhibited pain behavior and showed increased expression of P2X4 and the activated satellite glial cell (SGC) marker glial fibrillary acidic protein in dorsal root ganglia (DRG). AST treatment partly abrogated the upregulation of P2X4, inhibited SGC activation, and alleviated pain behavior in CCI rats; it also suppressed ATP-activated currents in HEK293 cells overexpressing P2X4. These data demonstrate that AST relieves neuropathic pain by inhibiting P2X4 and SGC activation in DRG, highlighting its therapeutic potential for clinical pain management.